Disentangling direct from indirect effects of habitat disturbance on multiple components of biodiversity. Issue 11 (12th September 2022) - Schwensow, Nina Isabell; Heni, Alexander Christoph; Schmid, Julian; Montero, B. Karina; Brändel, Stefan Dominik; Halczok, Tanja Katharina; Mayer, Gerd; Fackelmann, Gloria; Wilhelm, Kerstin; Schmid, Dominik Werner; Sommer, Simone
Abstract: Human habitat disturbance affects both species diversity and intraspecific genetic diversity, leading to correlations between these two components of biodiversity (termed species–genetic diversity correlation, SGDC). However, whether SGDC predictions extend to host‐associated communities, such as the intestinal parasite and gut microbial diversity, remains largely unexplored. Additionally, the role of dominant generalist species is often neglected despite their importance in shaping the environment experienced by other members of the ecological community, and their role as source, reservoir and vector of zoonotic diseases. New analytical approaches (e.g. structural equation modelling, SEM) can be used to assess SGDC relationships and distinguish among direct and indirect effects of habitat characteristics and disturbance on the various components of biodiversity. With six concrete and biologically sound models in mind, we collected habitat characteristics of 22 study sites from four distinct landscapes located in central Panama. Each landscape differed in the degree of human disturbance and fragmentation measured by several quantitative variables, such as canopy cover, canopy height and understorey density. In terms of biodiversity, we estimated on the one hand, (a) small mammal species diversity, and, on the other hand, (b) genome‐wide diversity, (c) intestinal parasite diversity and (d) gut microbial heterogeneity of the most dominant generalist species (Tome's spiny rat, Proechimys semispinosus ). We used SEMs to assess the links between habitat characteristics and biological diversity measures. The best supported SEM suggested that habitat characteristics directly and positively affect the richness of small mammals, the genetic diversity of P. semispinosus and its gut microbial heterogeneity. Habitat characteristics did not, however, directly impact intestinal parasite diversity. We also detected indirect, positive effects of habitat characteristics on both host‐associated assemblages via small mammal richness. For microbes, this is likely linked to cross species transmission, particularly in shared and/or anthropogenically altered habitats, whereas host diversity mitigates parasite infections. The SEM revealed an additional indirect but negative effect on intestinal parasite diversity via host genetic diversity. Our study showcases that habitat alterations not only affect species diversity and host genetic diversity in parallel, but also species diversity of host‐associated assemblages. The impacts from human disturbance are therefore expected to ripple through entire ecosystems with far reaching effects felt even by generalist species. Abstract : Given that anthropogenic disturbance is one of the most important factors influencing ecological communities, a better understanding of the reciprocity of the various components of biodiversity is needed to predict the development of disturbed natural communities. This study fills a critical gap in our understanding of the intimate interplay between anthropogenic habitat alterations and several layered components of biological diversity. It provides a possible explanation as to how anthropogenically altered and biologically depauperate habitats impact dominant generalist species that might become sources of diseases. Resumen: Las perturbaciones antropogénicas sobre los hábitats naturales pueden afectar tanto a la diversidad de las especies como a la diversidad genética intraespecífica, dando lugar a correlaciones entre estos dos elementos de la biodiversidad (denominados correlación de la diversidad genética de las especies, SGDC por sus siglas en inglés). Sin embargo, todavía queda sin explorar si las predicciones de la SGDC afectan a las comunidades de parásitos y microorganismos intestinales asociadas al hospedador. Adicionalmente, el rol que juegan las especies generalistas, especialmente aquéllas dominantes, suele ser descuidado, a pesar de la importancia de control que ejercen sobre la estructura de la comunidad, y su rol como fuente, reservorio y vector de enfermedades zoonóticas. Para poder evaluar las relaciones de SGDC y distinguir entre los efectos directos e indirectos que tienen las características del hábitat y las perturbaciones sobre los distintos componentes de la biodiversidad, se pueden utilizar nuevos enfoques analíticos como por ejemplo los modelos de ecuaciones estructurales (SEM, por sus siglas en inglés). Considerando seis modelos específicos y biológicamente sólidos, recopilamos las características del hábitat de 22 sitios ubicados en cuatro paisajes distintos situados en el centro de Panamá. Cada paisaje difería en el grado de perturbación antropogénica y fragmentación, medido por diferentes variables cuantitativas, como la cobertura del dosel, la altura del dosel y la densidad del sotobosque. En términos de biodiversidad, por un lado estimamos (1) la diversidad de especies de pequeños mamíferos y, por otro lado (2) la diversidad del genoma completo, (3) la diversidad de parásitos intestinales, y (4) la heterogeneidad de las comunidades microbianas del intestino de la especie generalista más dominante, la rata espinosa de Tomes Proechimys semispinosus . Para evaluar los vínculos entre las características del hábitat y las medidas de diversidad biológica se utilizó el modelado SEM. El SEM mejor apoyado sugirió que las características del hábitat afectan directa y positivamente a la abundancia de pequeños mamíferos, a la diversidad genética de P. semispinosus y a la heterogeneidad microbiana intestinal. Sin embargo, se observó que las características del hábitat no tienen un efecto directo en la diversidad de parásitos intestinales. Aparte de estos efectos directos, detectamos efectos indirectos y positivos de las características del hábitat en ambos conjuntos asociados al hospedador (diversidad de parásitos y microorganismos intestinales) a través de la abundancia de pequeños mamíferos. En el caso de las comunidades microbianas, esto está probablemente relacionado con la transmisión interespecífica, especialmente en hábitats compartidos y/o antropogénicamente alterados; mientras que la diversidad de hospedadores mitiga las infecciones de parásitos. El SEM reveló un efecto indirecto adicional pero negativo sobre la diversidad de parásitos intestinales a través de la diversidad genética de los hospedadores. Nuestro estudio muestra que los patrones de SGDC se filtran a través de las varias capas de diversidad biológica, añadiendo los ensamblajes asociados al hospedador como componentes biológicos afectados por las alteraciones del hábitat.